2002
DOI: 10.1038/sj.gt.3301814
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of chronic neuropathic pain after partial nerve injury by adeno-associated viral (AAV) vector-mediated over-expression of BDNF in the rat spinal cord

Abstract: Changing the levels of neurotrophins in the spinal cord micro-environment after nervous system injury has been proposed to recover normal function, such that behavioral response to peripheral stimuli does not lead to chronic pain. We have investigated the effects of recombinant adenoassociated viral (rAAV)-mediated over-expression of brainderived neurotrophic factor (BDNF) in the spinal cord on chronic neuropathic pain after unilateral chronic constriction injury (CCI) of the sciatic nerve. The rAAV-BDNF vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(60 citation statements)
references
References 75 publications
2
57
0
Order By: Relevance
“…intrathecal delivery of recombinant adeno-associated virus expressing the anti-inflammatory gene product human IL-10 or brain-derived neurotrophic factor has been shown to attenuate chronic neuropathic pain after partial nerve injury (32)(33)(34). These studies indicate that the i.t.…”
Section: Discussionmentioning
confidence: 57%
“…intrathecal delivery of recombinant adeno-associated virus expressing the anti-inflammatory gene product human IL-10 or brain-derived neurotrophic factor has been shown to attenuate chronic neuropathic pain after partial nerve injury (32)(33)(34). These studies indicate that the i.t.…”
Section: Discussionmentioning
confidence: 57%
“…However, blocking production of BDNF by dorsal root ganglia sensory neurons, showed that BDNF in dorsal root ganglia sensory neurons, while it contributed to inflammatory pain (induced by injections of either Carrageean, NGF or Formalin), it did not contribute to the development of neuropathic pain (following L5 spinal nerve ligation) (Zhao et al, 2006). Moreover, intrathecal application of BDNF has been shown to have both pronociceptive (Yajima et al, 2002;Yajima et al, 2005) and antinociceptive (Cejas et al, 2000;Eaton et al, 2002) effects following a peripheral nerve injury. These studies indicate that in order to establish that a molecular change within the dorsal root ganglia contribute to neuropathic pain requires more than a simple correlation between the observed molecular change and the presence of neuropathic pain.…”
Section: Peripheral Nerve Injury Alters the Dorsal Root Ganglia Envirmentioning
confidence: 99%
“…ates pain hypersensitivity induced by spinal nerve ligation (14), and overexpression of BDNF at the spinal level reduces neuropathic pain caused by sciatic nerve injury (15). At this time the mechanisms underlying prolonged KCC2 down-regulation in the spinal cord after nerve injury remain elusive.…”
mentioning
confidence: 99%